TECHNICAL CLASSIFICATION OF RAW MATERIALS FOR THE PRODUCTION OF BONE GLUE - Otamurodov, Jurabek Otaniyozovich (INTERNATIONAL CONFERENCES, 2022)
This material discusses the technical classification of raw materials and the classification of bone grades for the production of bone glue.